Optimalisasi Teknologi untuk Pemberdayaan SDM dan Manajemen Pemasaran di Desa Kuala Mandor - Pramana Saputra; Audriana Septiani Lo; Duhafilianisa; Kevin Wijaya; Yusuf Kurniawan.BM.; Charlie (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Technology continues to experience rapid development as times progress. The utilization of technology also continues to spread to all fields and aspects of human life. The use of technology helps various aspects to develop existing opportunities. In addition, human resource management (HRM) is very important for running company or organizational activities so that everything runs well and achieves targets. To succeed in a field, the implementation and development of human resources based on technology is needed in order to create quality human resources. In the current era, technology helps businesses to carry out more efficient digital innovations. Optimizing the use of technology became our main focus when conducting KKM-PKM activities in Kuala Mandor village. This proposal suggests a series of innovative activities aimed at developing the existing potential in Kuala Mandor village. The implementation of our work program also involves the participation of Kuala Mandor villagers. The innovative steps we take are providing education and digitalizing social media accounts for SMAN 1 Kuala Mandor and Keramba Cipta Mandiri. With this innovative step, Kuala Mandor village is expected to develop into a productive village and have a positive impact on the people involved.